2021
DOI: 10.3389/fpsyt.2020.585769
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut Microbiota in the High-Risk Construct of Severe Mental Disorders: A Mini Review

Abstract: Severe mental disorders (SMD) are highly prevalent psychiatric conditions exerting an enormous toll on society. Therefore, prevention of SMD has received enormous attention in the last two decades. Preventative approaches are based on the knowledge and detailed characterization of the developmental stages of SMD and on risk prediction. One relevant biological component, so far neglected in high risk research, is microbiota. The human microbiota consists in the ensemble of microbes, including viruses, bacteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…This could permit to ascertain whether changes in the composition of the gut microbiota correspond to major psychopathological modifications, establishing causality. While the analysis of drug-naïve patients would be particularly difficult in the case of TRS, given that this tends to be a mid/long term outcome in the clinical course of SCZ, and patients with TRS have, by definition, been exposed to several trials of antipsychotics, such an approach could be feasible only using establishing prospective cohorts followed in the long-term, as for high-risk studies [ 53 , 54 ]. Finally, translational approaches, including those using faecal transplant of the gut microbiota from more severe SCZ cases, such as TRS, into germ free animals, could lead to the identification of specific phenotypic alterations in animal models, and eventually of biosignature which can be reverse translated and validated in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This could permit to ascertain whether changes in the composition of the gut microbiota correspond to major psychopathological modifications, establishing causality. While the analysis of drug-naïve patients would be particularly difficult in the case of TRS, given that this tends to be a mid/long term outcome in the clinical course of SCZ, and patients with TRS have, by definition, been exposed to several trials of antipsychotics, such an approach could be feasible only using establishing prospective cohorts followed in the long-term, as for high-risk studies [ 53 , 54 ]. Finally, translational approaches, including those using faecal transplant of the gut microbiota from more severe SCZ cases, such as TRS, into germ free animals, could lead to the identification of specific phenotypic alterations in animal models, and eventually of biosignature which can be reverse translated and validated in humans.…”
Section: Discussionmentioning
confidence: 99%
“… 75 Besides, cross-sectional studies using nationally representative samples have observed that people with sleep disturbance had a low protein intake. 35 , 36 More recently, the role of microbiota on cognitive impairment 76 and severe mental disorders 77 has received increased attention. These data have important clinical implications since protein intake and microbiota are interconnected so that the structure and function of the microbiome might be impacted by protein quality, while it influences protein catabolism, digestion, and absorption.…”
Section: Discussionmentioning
confidence: 99%
“…In this index, greater distance indicates the greater difference between samples in the intestinal microbiota. In evaluations of the diversity of intestinal microbiota and various diseases, it was reported that many disease patients, for instance, lifestyle-related diseases, inflammatory diseases, mental disorders and infections, had a decreased α-diversity compared to healthy individuals [27][28][29][30][31][32][33][34][35][36], suggesting that the richness and evenness of intestinal microbiota have important roles on not only specific diseases but also general health conditions. This is likely because a decrease in α-diversity of intestinal microbiota causes a decline in the complementary/alternative functions of intestinal bacteria, making hosts vulnerable to changes in the external environment and susceptible to diseases [1].…”
Section: Introductionmentioning
confidence: 99%